Space Telescopes and Instrumentation 2018: Optical, Infrared, and Millimeter Wave 2018
DOI: 10.1117/12.2309421
|View full text |Cite
|
Sign up to set email alerts
|

Optical design of PICO: a concept for a space mission to probe inflation and cosmic origins

Abstract: The Probe of Inflation and Cosmic Origins (PICO) is a probe-class mission concept currently under study by NASA. PICO will probe the physics of the Big Bang and the energy scale of inflation, constrain the sum of neutrino masses, measure the growth of structures in the universe, and constrain its reionization history by making full sky maps of the cosmic microwave background with sensitivity 80 times higher than the Planck space mission. With bands at 21-799 GHz and arcmin resolution at the highest frequencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Both satellites would map hundreds of square degrees, with ∼10 ′′ , at 100 and 250 µm, respectively. A satellite targeting the entire sky, the Probe for Inflation and Cosmic Origins (PICO), has also been proposed (Sutin et al, 2018;Young et al, 2018). PICO would provide coverage in 10 frequency bands between 375 µm to 2 mm, with a best resolution of 1.1 ′ .…”
Section: Future Polarimetersmentioning
confidence: 99%
“…Both satellites would map hundreds of square degrees, with ∼10 ′′ , at 100 and 250 µm, respectively. A satellite targeting the entire sky, the Probe for Inflation and Cosmic Origins (PICO), has also been proposed (Sutin et al, 2018;Young et al, 2018). PICO would provide coverage in 10 frequency bands between 375 µm to 2 mm, with a best resolution of 1.1 ′ .…”
Section: Future Polarimetersmentioning
confidence: 99%
“…The bias in the value of r found from our simulations are less than 0.5-σ for the CMB missions such as Simons Observatory (Aguirre et al 2018) and LiteBIRD (Matsumura et al 2013) and hence are not going to contaminate the value of primordial gravitational wave signal severely. However, for the proposed CMB experiments with σ(r) 5 × 10 −4 such as CMB-S4 (Abazajian et al 2016), CMB-Bharat 7 and PICO (Young et al 2018;Hanany et al 2019), the bias in the value of r can be greater than 1-σ as shown in Figure 5. The amount of bias varies with the model of reionization and may be difficult to estimate this bias robustly from CMB polarization data alone.…”
Section: Resultsmentioning
confidence: 98%
“…A possible source of secondary anisotropy is the B-mode polarization arising from the patchy electron distribution during reionization. This can potentially contaminate the recombination bump of the B-mode polarization leading to a bias in the inferred value of r. Hence an accurate and reliable computation of the signal arising from reionization is crucial for the upcoming experiments that aim to detect the primordial B-modes (Matsumura et al 2013;Aguirre et al 2018;Abazajian et al 2016;Young et al 2018). As per the current understanding, reionization is an inhomogeneous and complex process (Mesinger & Furlanetto 2007;Zahn et al 2007;Choudhury et al 2009;Mitra et al 2018) which depends on various astrophysical processes related to early galaxy formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A future data-driven model of the galactic magnetic field in future will allow making more precise statements. Future experiments such as Simons Observatory [61], Simons Array [62], Adv-ACT [63], SPT-3G [62] and proposed missions like CMB-S4 [64], LiteBIRD [65], CMB-Bharat, PIXIE [66] and PICO [67] will improve these constraints significantly. Future CMB experiments having more frequency channels will play a crutial role in removing the contamination from CMB fluctuations and the galactic foregrounds.…”
Section: Resultsmentioning
confidence: 99%